EFEKTIVITAS MANGO (MANGA NIHONGO) TERHADAP PENINGKATAN HASIL PEMBELAJARAN TATA BAHASA JEPANG DI SMA NEGERI 110 JAKARTA - Sundawi, Siti Febrianti; Nur Saadah Fitri Asih; Nia Setiawati (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2025)
This study aims to investigate the effectiveness of using Mango (Manga Nihongo) on Japanese grammar learning outcomes. The background of this research is the difficulties faced by students in understanding sentence structure and verb changes in Japanese, as well as student boredom with learning media that are less varied during distance learning. This study used a preexperimental one group pretest and posttest method with 32 students of class XII-Language at SMA Negeri 110 Jakarta as samples. The instruments used were tests and questionnaires. Based on the results of data processing using the paired sample t-test formula, it was found that the Sig. (2-tailed) value was 0.000 with t_count of 12.30 at a significance level of 5% with t_table of 2.04. This shows that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. The Normalized gain calculation results show a value of 0.66 which is in the medium category with a percentage of 66.14% which shows that Mango (Manga Nihongo) media is quite　effective for improving Japanese grammar learning outcomes. This media provides a new learning experience using digital comics that can be accessed anytime and anywhere, so it can motivate students and improve learning outcomes.